Virtual Pulpit: Da'wah Innovation and Tips to Survive in the Digital Information Vortex - Farhan Dimas Subagja (Advances In Social Humanities Research, 2026)
The rapid development of digital technology has transformed various aspects of human life, including religious communication and da'wah activities. Traditional da'wah, which was predominantly conducted through physical pulpits in mosques and religious institutions, has increasingly shifted to digital platforms such as WhatsApp, Instagram, TikTok, and YouTube. This transformation creates both opportunities and challenges, particularly in navigating the overwhelming flow of digital information and misinformation. Therefore, this study aims to examine the transition of da'wah from the physical pulpit to the virtual world, identify innovations in digital da'wah practices, and formulate strategies for sustaining da'wah in the digital information vortex. This research employs a qualitative observational approach by analyzing digital da'wah practices across various social media platforms. Data were collected through observations of content formats, audience engagement patterns, and challenges encountered in digital religious communication. The findings reveal that digital media have significantly expanded the reach of da'wah, enabled interactive communication between preachers and audiences, and encouraged the adoption of innovative content formats such as short videos, podcasts, and live streaming. However, challenges such as misinformation, credibility issues, content verification difficulties, and algorithmic barriers remain significant concerns. The study concludes that the sustainability of digital da'wah depends on digital literacy, information verification, ethical communication practices, and adaptation to platform-specific characteristics. The research implies that religious institutions, preachers, and digital content creators should strengthen collaborative efforts, improve digital literacy competencies, and develop credible standards for online religious content to ensure the effectiveness and integrity of da'wah in the contemporary digital era.